Diaquabis{5-carboxy-2-[(1H-1,2,4-triazol-1-yl)methyl]-1H-imidazole-4-carboxylato}manganese(II) - Ding, De-Gang (International Union of Crystallography, 2010)
In the title compound, [Mn(C(8)H(6)N(5)O(4))(2)(H(2)O)(2)], the Mn(II) ion is situated on an inversion center and is six-coordinated by two N and two O atoms from two L ligands (HL = 2-[(1H-1,2,4-triazol-1-yl)methyl]-1H-imidazole-4,5-dicarboxylic acid) and two water molecules in a distorted octahedral geometry. In ligand L, the imidazole and triazole rings form a dihedral angle of 74.25 (8)°. Molecules are assembled into a three-dimensional structure via intermolecular O—H⋯O, O—H⋯N and N—H⋯N hydrogen-bonds, and π–π interactions with a short distance of 3.665 (2) Å between the centroids of the imidazole and triazole rings of neighbouring molecules.